Test-retest reliability of IPAQ environmental- module in an African population - Oyeyemi Adetoyeje Y; Adegoke Babatunde OA; Oyeyemi Adewale L; Fatudimu Bukola M (BMC, 2008)
Abstract Background There is overwhelming evidence of the benefits of physical activity and the physical environment is increasingly recognized as a promising determinant of physical activity participation. The influence of the environment on physical activity has not been evaluated among black Africans and no specific measure exists for assessing environmental factors related to physical activity in an African environment. The IPAQ E- module was designed to assess environmental factors for physical activity participation and was considered to be relevant to all countries regardless of the stage of economic development. The objective of this study was to assess the test- retest reliability of IPAQ E- module in an African population. Methods One hundred and three clinical students of a University in Nigeria were invited to participate in the reliability testing of IPAQ E- module. Sixteen of the 17- items on the environmental measure were assessed for test- retest reliability using intraclass correlation coefficient (ICC) with 95% Confidence interval (CI) overall and by gender. The measure addressed items regarding residential density, access to destinations, neighborhood infrastructures, aesthetic qualities, social environment, street connectivity and neighborhood safety. Results Of the total respondents, 51.5% were males and 48.5% were females. Overall, the intraclass correlation coefficient (ICC) ranged from 0.43 to 0.91. The item regarding many interesting things to look at (aesthetic) produced the overall highest reliability score (ICC = 0.91, 95% CI = 0.86 - 0.94), while the item regarding safety from crime during the day (neighborhood safety) produced the lowest overall score (ICC = 0.43, 95% CI = 0.26 - 0.57). Reliability of items on neighborhood infrastructures ranged between substantial agreement to almost perfect agreement overall (ICC = 0.66 - 0.88) and by gender (male- ICC = 0.68 - 0.90 and female- ICC = 0.63 - 0.86). The access to destination items (ICC = 0.49 - 0.74), social environment (ICC = 0.62) and street connectivity (ICC = 0.78) all had acceptable reliability overall. Meaningful differences were found between males and females on two items on neighborhood safety and one item on access to destinations. Conclusion The test- retest of IPAQ E- module resulted in moderate to almost perfect agreement for most of the items with few meaningful differences by gender. Environmental items of physical activity in an African population exhibited reliability similar to that in other environments. These results suggest that IPAQ E- module may be a useful measure for assessing environmental correlates of physical activity among population in Africa.